2021
DOI: 10.1177/21582440211009469
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Education and Women: Voices From Pakistan

Abstract: This article aims at investigating the relevance of a gender perspective in societies where women are mainly responsible for the household and childcare. For this purpose, the activities of two environmental and women’s empowerment–related nongovernmental organizations (NGOs) from Pakistan, Leadership for Environment and Development (LEAD) and Aurat (woman) Foundation, have been investigated with the help of a case study methodology. Semi-structured interviews have been conducted with 12 females. Through a fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…These researchers believed that females have a significant concern for environmental education as compared to men. The study of Imran, Akhtar, Chen, and Ahmad (2021) also confirmed that women play an interactive role in the awareness of environmental education. The findings suggest that women's awareness regarding environmental education can be used as a tool for women's empowerment and assessment to make a greater impact on the sustainability of their communities.…”
Section: Discussionsupporting
confidence: 56%
“…These researchers believed that females have a significant concern for environmental education as compared to men. The study of Imran, Akhtar, Chen, and Ahmad (2021) also confirmed that women play an interactive role in the awareness of environmental education. The findings suggest that women's awareness regarding environmental education can be used as a tool for women's empowerment and assessment to make a greater impact on the sustainability of their communities.…”
Section: Discussionsupporting
confidence: 56%
“…economic status of participants and their consciousness of environmental and health-related issues [47][48][49].…”
Section: Plos Onementioning
confidence: 99%
“…6 , ELT teachers in central districts of Punjab need professional training in the latest technologies used in developed countries, as well as subject development courses such as TESOL (Teachers of English to Speakers of Other Languages), TEFL (Teaching of English as Foreign Language), and PEELI (Punjab Education and English Language Initiative). This training will enhance their ability to integrate technology with teaching in their classrooms [ 39 , 40 ]. To address this need, specific professional courses or certifications related to ELT teaching should be added as prerequisites to the qualifications of teachers involved in ELT teaching courses at all levels throughout the country.…”
Section: Findings and Discussionmentioning
confidence: 99%